Home Environments and Preschoolerâ€™s Bullying Behaviour - Eweniyi, Iyabode T.; Omotere, Adunola H. (NIU Journal of Social Sciences, 2020)
A child who exhibits aggressive behaviour that affects his or her relationship with other children around him or her is termed having behavioural problems. The study examined the influence of home environments on bullying behaviour among preschool pupils in Ijebu-ode local government area of Ogun State. Three research questions were raised and answered in this study. This study adopted the descriptive survey research design. The target population for this study consists of all parents, caregivers and pupils in the forty three (43) government owned preschools in Ijebu-Ode Local Government area of Ogun State. Three research instruments tagged â€œHome Environment and Children Bullying Behaviour" (HECBB), "Class Bullying Assessment Scale" (CBAS) and the self- observation report from the researcherâ€ were developed and used for this study. The data collected were analyzed using ANOVA and Pearson's Correlation Coefficient. The result revealed that bullying incidence is not significant or related to home location. The result shows that there is no significant influence of neigbourhood characteristics on bullying incidence among preschoolers. The result shows that parents' occupation has a significant influence on bullying incidence among preschoolers. Based on the findings, it was recommended that: Schools should organize training for parents on what bullying is, what the school's policies and rules are, and how the enforcement of the rules may affect the child and the Caregivers should make provision of measures to control bullying incidence among preschoolers and help them to engross healthy behaviour in their pupils. Keywords: Preschooler, Home Environments, Bullying Behaviour